Extracorporeal life support in therapy-refractory cardiocirculatory failure: looking beyond 30 days. (21st December 2020) - Guenther, Sabina P W; Hornung, Roman; Joskowiak, Dominik; Vlachea, Polyxeni; Feil, Katharina; Orban, Martin; Peterss, Sven; Born, Frank; Hausleiter, Jörg; Massberg, Steffen; Hagl, Christian
Abstract: OBJECTIVES: Venoarterial extracorporeal life support (ECLS) has emerged as a potentially life-saving treatment option in therapy-refractory cardiocirculatory failure, but longer-term outcome is poorly defined. Here, we present a comprehensive follow-up analysis covering all major organ systems. METHODS: From February 2012 to December 2016, 180 patients were treated with ECLS for therapy-refractory cardiogenic shock or cardiac arrest. The 30-day survival was 43.9%, and 30-day survivors ( n = 79) underwent follow-up analysis with the assessment of medium-term survival, quality of life, neuropsychological, cardiopulmonary and end-organ status. RESULTS: After a median of 1.9 (1.1–3.6) years (182.4 patient years), 45 of the 79 patients (57.0%) were alive, 35.4% had died and 7.6% were lost to follow-up. Follow-up survival estimates were 78.0% at 1, 61.2% at 3 and 55.1% at 5 years. NYHA class at follow-up was ≤II for 83.3%. The median creatinine was 1.1 (1.0–1.4) mg/dl, and the median bilirubin was 0.8 (0.5–1.0) mg/dl. No patient required dialysis. Overall, 94.4% were free from moderate or severe disability, although 11.1% needed care. Full re-integration into social life was reported by 58.3%, and 39.4% were working. Quality of life was favourable for mental components, but a subset showed deficits in physical aspects. While age was the only peri-implantation parameter significantly predicting medium-term survival, adverse events and functional status at discharge or 30 days were strong predictors. CONCLUSIONS: This study demonstrates positive medium-term outcome with high rates of independence in daily life and self-care but a subset of 10–20% suffered from sustained impairments. Our results indicate that peri-implantation parameters lack predictive power but downstream morbidity and functional status at discharge or 30 days can help identify patients at risk for poor recovery.